Resin-attached aluminum pigment, coating material, and ink

The resin-coated aluminum pigment addresses the issues of chemical resistance and dispersion in conventional aluminum pigments by attaching resin grains to the edges, enhancing adhesion and design properties.

JP2025011960APending Publication Date: 2025-01-24ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023114437
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Conventional aluminum pigments lack sufficient chemical resistance, particularly to alkalis, and suffer from aggregation and poor dispersion in paints, which affects their design and adhesion properties.

Method used

A resin-coated aluminum pigment is developed with resin grains attached to the edges of aluminum particles, featuring a specific diameter range and distribution, enhancing chemical resistance and adhesion while maintaining design qualities.

Benefits of technology

The resin-coated aluminum pigment exhibits improved chemical resistance, especially to alkalis, with enhanced adhesion and dispersion, resulting in better paint performance and design qualities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011960000001_ABST
    Figure 2025011960000001_ABST
Patent Text Reader

Abstract

To provide a resin-attached aluminum pigment which has excellent designability, and excellent adhesion and chemical resistance.SOLUTION: There is provided a flat resin-attached aluminum pigment in which the surface of aluminum particles are coated with a resin layer containing a monomer having one or more radical-polymerizable double bonds and / or a polymer of an oligomer, wherein resin particles having a circle-equivalent diameter of 5 to 50 nm are attached onto an arbitrary edge part of the resin-attached aluminum pigment.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin-deposited aluminum pigment, and to paints and inks containing the resin-deposited aluminum pigment. [Background technology]

[0002] Aluminum pigments have been used for a long time in metallic paints, printing inks, plastic mixing, etc., to obtain a cosmetic effect that emphasizes a metallic feel. In particular, thin-film aluminum with an average particle size of 20 μm or less and a particle thickness of 0.1 μm or less has excellent design properties. On the other hand, by coating these aluminum pigments with resin, it is possible to improve chemical resistance to chemicals such as alkali resistance.

[0003] As a method for improving the alkali resistance of aluminum pigments as described above, a method of subjecting the aluminum pigments to a specific surface treatment has been proposed. For example, Patent Document 1 describes that a pigment having excellent chemical resistance to chemicals such as alkalis can be provided by setting the ratio of the total area of ​​resin particles having an equivalent circle diameter of 25 nm or more on the surface of the coating resin that coats the surfaces of aluminum particles to a specific range. However, there is no description about agglomeration due to interactions between aluminum particles or dispersibility of the pigment in paint.

[0004] Patent Document 2 describes how a metallic pigment can be provided that has improved affinity and adhesion with binder resins such as paints and has improved peel resistance for coating films and printed surfaces, without substantially reducing gloss, by leaving part of the surface of the metallic pigment particles and forming synthetic resin protrusions here and there on the remaining surface of the metallic pigment particles. However, there is no description of chemical resistance to chemicals such as alkalis, nor is there any description of cohesiveness due to interactions between aluminum particles, or dispersibility of the pigment in paint. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2018 / 047360 [Patent Document 2] JP 2001-115061 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention aims to provide a resin-adhered aluminum pigment, which has not necessarily been fully realized by the above-mentioned conventional techniques, and aims to provide a resin-adhered aluminum pigment having excellent design properties as well as excellent adhesion and chemical resistance by improving the dispersibility of the resin-adhered aluminum pigment in paint. [Means for solving the problem]

[0007] As a result of intensive research aimed at solving the above-mentioned problems, the inventors have discovered that by arranging resin particles near the edges of a resin-adhered aluminum pigment, it is possible to obtain a resin-adhered aluminum pigment that has improved paint dispersibility, excellent design properties, and excellent adhesion and chemical resistance to chemicals such as alkalis, and have thus completed the present invention. That is, the gist of the present invention is as follows. [1] A flat resin-attached aluminum pigment in which the surface of an aluminum particle is coated with a resin layer containing a polymer of a monomer / oligomer having one or more radically polymerizable double bonds, The resin-adhered aluminum pigment has resin particles having a circle-equivalent diameter of 5 to 50 nm adhered to any edge portion of the resin-adhered aluminum pigment. [2] A flat resin-attached aluminum pigment in which the surfaces of aluminum particles are coated with a resin layer containing a polymer of a monomer and / or oligomer having one or more radically polymerizable double bonds, The resin-adhered aluminum pigment has, on an edge portion of the resin-adhered aluminum pigment, 3 to 1000 resin particles having a circle equivalent diameter of 5 to 50 nm adhered per 5 μm length of the edge portion. [3] The resin-adhered aluminum pigment according to the above [2], wherein 3 to 100 resin particles having a circle equivalent diameter of 5 to 50 nm are adhered to an edge portion of the resin-adhered aluminum pigment per 5 μm of length of the edge portion. [4] The resin-adhered aluminum pigment according to the above [2], wherein 10 to 100 resin particles having a circle equivalent diameter of 5 to 50 nm are adhered to an edge portion of the resin-adhered aluminum pigment per 5 μm of length of the edge portion. [5] The resin-adhered aluminum pigment according to the above [2], wherein the average surface roughness Ra of the resin layer is 2.0 to 7.0 nm. [6] The resin-adhered aluminum pigment according to the above-mentioned [2], wherein the proportion of the portion of the resin layer where the thickness τ of the resin layer is 5 nm or less, as observed by cross-sectional observation of the resin-adhered aluminum pigment, is 5% or less. [7] The resin-adhered aluminum pigment according to the above [2], wherein the aluminum particles have an average cross-sectional thickness τ' of 0.03 to 0.18 μm and an average particle diameter d50 of 5 to 15 μm. [8] A paint containing the resin-adhered aluminum pigment according to any one of the above [2] to [7]. [9] An ink containing the resin-adhered aluminum pigment according to any one of [2] to [7] above. Effect of the Invention

[0008] According to the present invention, it is possible to provide a resin-adhered aluminum pigment that has not necessarily been fully realized by conventional techniques, and it is possible to provide a resin-adhered aluminum pigment with improved dispersibility in paint, excellent design properties, and excellent adhesion and chemical resistance. [Brief description of the drawings]

[0009] [Figure 1] 1 is an example of a SEM photograph of the resin-adhered aluminum pigment of Example 1. [Diagram 2] 2 is an example of an SEM photograph of the resin-adhered aluminum pigment of Example 1, which is a higher magnification of the SEM photograph of FIG. 1. [Diagram 3] 1A and 1B are both examples of AFM photographs of the resin-adhered aluminum pigment of Example 1, where (a) is a bird's-eye view and (b) is a height image. [Figure 4] 1 is an example of a TEM photograph of a cross section of the resin-adhered aluminum pigment of Example 1. [Diagram 5] 1 is an example of a microscope photograph of a metallic base coated plate using the resin-adhered aluminum pigment of Example 1. [Figure 6] 1 is an example of a SEM photograph of the resin-adhered aluminum pigment of Comparative Example 1. [Figure 7] 1 is an example of a TEM photograph of a cross section of a resin-adhered aluminum pigment of Comparative Example 1. [Figure 8] 1 is an example of a microscope photograph of a metallic base coated plate using the resin-adhered aluminum pigment of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an example of a preferred embodiment of the present invention will be described. However, the following embodiment is merely an example for explaining the present invention, and the present invention is not limited to the following embodiment.

[0011] The resin-adhered aluminum pigment of the present invention has excellent adhesion and chemical resistance while maintaining excellent design properties.

[0012] The specific shapes of the aluminum particles that are the raw material for the resin-adhered aluminum pigment of the present invention will be described below.

[0013] The aluminum particles used in the present invention (hereinafter, sometimes referred to as "flake aluminum powder") are not limited in type, and may be those generally used as aluminum pigments, and have a flat shape such as a scaly, angular, rounded, etc. If high designability (e.g., properties such as brightness, brilliance, flip-flop feel, and hiding power) is to be maintained, the effect of the present invention will be more pronounced if high design grade aluminum particles (grade for vapor deposition metallic paint or ink) are used.

[0014] The method for producing the flaky aluminum powder is not particularly limited, but the powder can be obtained by pulverizing granular powder or small pieces of metallic aluminum together with a few percent of a grinding aid by a mechanical method such as a stamp mill method, a dry ball mill method, a wet ball mill method, an attritor method, or a vibrating ball mill method.

[0015] Examples of methods for producing highly decorative flaky aluminum powder include the method described in WO 99 / 54074. The flaky aluminum powder obtained by this method, which has a smooth surface and uniform thickness, can be particularly preferably used as the raw material for the aluminum pigment of the present invention.

[0016] The particle size of the aluminum particles used as the raw material for the resin-adhered aluminum pigment of the present invention varies depending on the application. When the resin-adhered aluminum pigment of the present invention is used for paints and printing inks, aluminum particles with an average particle size d50 (μm) of about 1 to 100 μm can be suitably used. In addition, applications in which high designability of metal pigments is particularly required recently include automobiles, general home appliances, and information appliances such as mobile phones, and in these applications, metal pigments are used to paint metals such as iron and magnesium alloys or plastics. In order to ensure high designability, the preferred average particle size (d50) of the aluminum particles of the resin-adhered aluminum pigment of the present invention used for these applications is 5 to 35 μm, and more preferably 5 to 15 μm.

[0017] The average particle size d50 (μm) of the aluminum particles of the present invention can be measured using a general laser diffraction / scattering type particle size distribution measuring device, and can be measured, for example, as follows. The average particle size (d50) of the particles of the flaky aluminum powder is measured using a laser diffraction / scattering type particle size distribution measuring device (LA-300 / Horiba, Ltd.) Mineral spirits can be used as the measurement solvent. It is preferable that the resin-adhered aluminum pigment sample is subjected to ultrasonic dispersion for 2 minutes as a pretreatment, then placed in a dispersion tank and the measurement is started after confirming that the appropriate concentration has been achieved.

[0018] The average cross-sectional thickness τ' (μm) of the aluminum particles of the present invention can be determined by using an FE-SEM image of the cross section of the coating film and measuring it with the aid of image analysis software. Specifically, 100 particles are randomly selected from an FE-SEM image of the cross section of the coating film, the cross-sectional thickness of the particles is automatically measured, and the arithmetic average value of the 100 particles is calculated. The average cross-sectional thickness τ' (μm) of the aluminum particles of this embodiment is preferably 0.03 to 0.20 μm, and more preferably 0.03 to 0.15 μm.

[0019] The specific composition and shape of the resin adhered to the surface of the aluminum pigment of the present invention will be described below.

[0020] The resin adhered to the resin-adhered aluminum pigment of this embodiment is not particularly limited, but is preferably a polymer of a monomer (hereinafter referred to as a monomer) and / or an oligomer having one or more radically polymerizable double bonds.

[0021] The monomer is not particularly limited, and any monomer known in the art can be used. Specific examples include, but are not limited to, unsaturated carboxylic acids (e.g., acrylic acid, methacrylic acid, itaconic acid, fumaric acid, citraconic acid, crotonic acid, maleic acid or maleic anhydride), mono- or diesters of phosphorus or phosphonic acid (e.g., 2-methacryloyloxyethyl phosphate, di-2-methacryloyloxyethyl phosphate, tri-2-methacryloyloxyethyl phosphate, 2-acryloyloxyethyl phosphate, di-2-acryloyloxyethyl phosphate, tri-2-acryloyloxyethyl phosphate, diphenyl-2-acryloyloxyethyl phosphate, dibutyl-2-methacryloyloxyethyl phosphate, dioctyl-2-acryloyloxyethyl phosphate, 2-methacryloyloxypropyl phosphate, bis(2-chloroethyl)vinyl phosphonate, diallyl dibutyl phosphonosuccinate, 2-methacryloyloxyethyl phosphate, 2- ... ethyl phosphate), coupling agents (e.g., γ-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, vinyltrichlorosilane, vinyltriethoxysilane, vinyltrimethoxysilane, vinyltris(β-methoxyethoxy)silane, isopropylisostearoyldiacryl titanate, acetoalkoxyaluminum diisopropylate, zircoaluminate), nitriles of unsaturated carboxylic acids (e.g., acrylonitrile, methacrylonitrile), or esters of unsaturated carboxylic acids (e.g., methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, lauryl acrylate, stearyl acrylate, hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methoxyethyl acrylate, butoxyethyl acrylate, glycidyl acrylate, cyclohexyl acrylate, 1,6-hexanediol diacrylate, 1,4-Butadiol diacrylate, triethylene glycol diacrylate, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, neopentyl glycol dimethacrylate, trimethylolpropane triacrylate, tetramethylolpropane tetraacrylate, tetramethylolpropane methane triacrylate, trimethylolpropane trimethacrylate, tetramethylolmethane trimethacrylate, di-trimethylolpropane tetraacrylate, pentaerythritol tetraacrylate, di-pentaerythritol Preferred examples of the methacrylates that can be used include thritol hexaacrylate, di-pentaerythritol pentaacrylate, di-pentaerythritol pentaacrylate monopropionate, triacrylformal, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, lauryl methacrylate, stearyl methacrylate, hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, methoxyethyl methacrylate, butoxyethyl methacrylate, glycidyl methacrylate, and cyclohexyl methacrylate. Furthermore, cyclic unsaturated compounds (e.g., cyclohexene) and aromatic unsaturated compounds (e.g., styrene, α-methylstyrene, vinyltoluene, divinylbenzene, cyclohexene vinyl monoxide, divinylbenzene monoxide, vinyl acetate, vinyl propionate, allylbenzene, or diallylbenzene) can also be suitably used. Furthermore, cyclic unsaturated compounds (e.g., cyclohexene) and aromatic unsaturated compounds (e.g., styrene, α-methylstyrene, vinyltoluene, divinylbenzene, cyclohexene vinyl monoxide, divinylbenzene monoxide, vinyl acetate, vinyl propionate, allylbenzene, or diallylbenzene) can also be suitably used. The oligomer having one or more radically polymerizable double bonds can be a polymer of these monomers.

[0022] In the method for producing a resin-adhered aluminum pigment of this embodiment, the amount of the monomer and / or oligomer added to the aluminum particles is, for example, preferably 5% or more, more preferably 8% or more, 10% or more, or 15% or more. By adding the amount of the monomer and / or oligomer to the aluminum particles at or above the lower limit, a resin layer is formed on the surface of the aluminum particles, and resin particles are formed at the edge portions of the resin-adhered aluminum pigment. If the amount of the monomer and / or oligomer added is below the lower limit, a resin layer and resin particles are not sufficiently formed on the surface of the aluminum particles.

[0023] In the method for producing a resin-adhered aluminum pigment of this embodiment, it is preferable to use a radical polymerization initiator (hereinafter, referred to as a polymerization initiator). The polymerization initiator is generally known as a radical generator, and the type thereof is not particularly limited. Examples of the polymerization initiator include, but are not limited to, peroxides such as benzoyl peroxide, lauroyl peroxide, and bis-(4-t-butylcyclohexyl)peroxydicarbonate, and azo compounds such as 2,2'-azobis-isobutyronitrile, 2,2'-azobis-2,4-dimethylvaleronitrile, and 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile.

[0024] The amount of polymerization initiator used is a factor that determines the molecular weight of the resin particles. When the amount of polymerization initiator is 0.5 molar equivalents or less relative to the amount of monomer, the molecular weight increases due to the small amount of polymerization initiator, leading to a decrease in design. When the amount is 2.0 molar equivalents or more, the amount of polymerization initiator is excessive, and a termination reaction occurs between the initiators, which makes the generated resin particles easy to slide off, and may cause bumps (irregularities on the coating film surface) on the coating film. For these reasons, the amount of polymerization initiator used is preferably, for example, 0.5 molar equivalents or more and less than 2.0 molar equivalents relative to the monomer.

[0025] The solvent is not limited to the following examples, but the organic solvent used to disperse the metal pigment in the organic solvent may be inactive against the metal pigment, and examples of the organic solvent include aliphatic hydrocarbons such as hexane, heptane, octane, and mineral spirits, aromatic hydrocarbons such as benzene, toluene, xylene, and solvent naphtha, ethers such as tetrahydrofuran and diethyl ether, alcohols such as ethanol, 2-propanol, and butanol, esters such as ethyl acetate and butyl acetate, glycols such as propylene glycol and ethylene glycol, glycol ethers such as propylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, and ethylene glycol monobutyl ether, and glycol esters such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and ethylene glycol monomethyl ether acetate. These organic solvents may be used alone or in combination of two or more. In the present invention, the organic solvent is also used as a reaction solvent when forming a resin by polymerizing the above-mentioned monomers and / or oligomers.

[0026] In one embodiment of the present invention, the resin-adhered aluminum pigment has resin particles having a circle-equivalent diameter (more specifically, area-equivalent circle diameter; Heywood diameter) of 5 to 50 nm attached to any edge portion thereof, i.e., compared to the surface of a flat aluminum particle, the resin particles are specifically attached to at least a portion of the edge portion. In one embodiment of the present invention, the resin-adhered aluminum pigment has resin particles having a circle equivalent diameter of 5 to 50 nm attached to its edge portion, preferably 10 to 1,000 particles, more preferably 3 to 100 particles, and even more preferably 10 to 100 particles per 5 μm length in any portion constituting the edge portion (any part of the outer periphery of the resin-adhered aluminum pigment). The edge portion refers to the end (outer edge portion) and the area immediately adjacent thereto of the resin-coated aluminum pigment having a flat shape such as a scale-like, angular, or rounded shape as shown in FIG. In the manufacturing process of the resin-attached aluminum pigment of the present invention, it is preferable to carry out the polymerization reaction while maintaining the primary particle state by using various high-speed stirring means such as a kneader, a two-roll mill, a three-roll mill, a ball mill, a horizontal sand mill, a vertical sand mill, an annular bead mill, or an attritor, from dispersing aluminum particles in a solvent until the polymerization of the monomer and the end of the reaction. This process increases the interaction between particles, selectively attaches resin particles to edge portions, and maintains the smoothness of the surface.

[0027] Regarding the stirring speed of the resin-adhered aluminum pigment of the present invention, if a load of 10,000 rpm or more is applied, the aluminum particles may be damaged, and if it is 700 rpm or less, there is a possibility that the aluminum particles may aggregate when the resin is adhered to them. Therefore, the stirring speed is preferably 700 to 10,000 rpm, and more preferably 700 to 2,000 rpm.

[0028] The resin-attached aluminum pigment of the present invention is characterized by high design retention and chemical resistance to chemicals such as alkali, compared to thin-film aluminum pigments. This is characterized by having a resin layer and forming minute resin particles at the edge portions by reacting a monomer at a high polymerization initiator concentration (e.g., 0.5 molar equivalents or more and less than 2.0 molar equivalents) with a monomer amount sufficient for maintaining alkali resistance and design (e.g., the amount of monomer and / or oligomer added to the aluminum particles is 5% or more) under high-speed stirring. High-speed stirring increases the interaction between the aluminum pigments, making it difficult for the resin particles to adhere to areas other than the edges of the aluminum particles, and it is believed that the selective formation of resin particles at the edge portions improves the dispersibility of the resin-attached aluminum pigment in the paint. It is believed that improved paint dispersibility improves the hiding power and color tone of the paint, resulting in a paint with excellent design. For resin-adhered aluminum pigments, the number of resin particles at the edge can be evaluated from SEM images, the formation of a smooth resin layer can be evaluated from AFM measurement data, and the formation of the resin layer can be evaluated from TEM images. These evaluation methods are explained below with specific examples, but the equipment used and measurement conditions can be changed within the range in which appropriate evaluation results can be obtained.

[0029] [Amount of resin particles per 5μm at the edge (A) measured by SEM] The resin-coated aluminum pigment is diluted with an excess of pentane, hand-dispersed for 1 minute, and the resulting solution is air-dried to obtain a measurement sample of the resin-coated aluminum pigment. Next, gold is vapor-deposited on the measurement sample, and the pigment side is observed from an angle of 45° using a scanning electron microscope (e.g., SEM JSM7800F manufactured by JEOL Ltd.) and evaluated. The measurement magnification is, for example, 10,000 times. The resin-adhered aluminum pigment is observed in 30 fields of view, and the projected area circle equivalent diameter (circle equivalent diameter) of the resin particles is measured. The amount of resin particles with a circle equivalent diameter of 5 to 50 nm present at the edge portion of the resin-adhered aluminum pigment is determined using image analysis software (e.g., Win Roof version 5.5 (manufactured by MITANI CORPORATION)), and then the number of resin particles, which are primary particles present on the 5 μm edge portion, is determined, and the arithmetic average value (A) is calculated.

[0030] The equivalent circle diameter of the resin particles present on the edge portions of the resin-adhered aluminum pigment of the present invention is preferably from 5 to 50 nm, and more preferably from 5 to 40 nm. The number (A) of the resin particles present per 5 μm length of the edge portion is preferably 3 to 1,000, more preferably 3 to 100, and even more preferably 10 to 100.

[0031] The average surface roughness Ra of the resin layer surface of the resin-adhered aluminum pigment of the present invention is 2.0 to 7.0 nm. The average surface roughness Ra referred to in the present invention can be calculated by a surface morphology observation method using a general atomic force microscope. Specifically, it is calculated, for example, by the following method. An atomic force microscope (hereinafter abbreviated as AFM) (e.g., Dimensioin Icon (manufactured by Bruker)) can be used to observe the surface morphology of resin-attached aluminum pigments. For pretreatment, for example, a resin-attached aluminum pigment sample is washed with excess methanol, vacuum-dried, dispersed again in acetone, dropped onto a Si wafer, and naturally dried. Quantification of surface roughness using AFM is performed for resin-attached aluminum pigments that do not overlap with other resin-attached aluminum pigments, with a measurement field of view of 2 μm and 512 pixels, and the calculated average value is defined as the "average surface roughness Ra (nm)." Surface roughness terminology is based on JIS-B-0601:2013. The average surface roughness Ra of the resin-attached aluminum pigment of the present invention is usually 10.0 nm or less, preferably 7.0 nm or less. When the average surface roughness Ra is 7.0 or less, the regular reflectance of light on the surface is high, so that the light shows extremely excellent light brightness and also has good flop properties. In addition, an average surface roughness Ra of 7.0 or less indicates that there are no resin particles on the surface of the resin-attached aluminum pigment other than the edge parts, or that only a very small amount of resin particles are attached.

[0032] In the resin-adhered aluminum pigment of the present invention, the thickness τ of the resin layer measured by observing a cross section of the resin-adhered aluminum pigment is preferably 5 to 30 nm, more preferably 10 to 20 nm. When the thickness τ of the resin layer is within this range, the pigment exhibits extremely excellent high brightness and good chemical resistance. In addition, in the resin-adhered aluminum pigment of the present invention, the proportion of the portion of the resin layer having a thickness of 5 nm or less is preferably 5% or less.

[0033] [Proportion of aluminum pigment interfaces with resin layer thickness τ of 5 nm or less as measured by TEM (B)] The average thickness τ of the resin layer in the present invention is first pretreated by ultrasonically cleaning the resin-attached aluminum pigment with excess methanol and chloroform, then vacuum drying, dispersing and cleaning again in acetone, and then air drying. Then, the resin is embedded in epoxy resin and completely cured, then trimmed and cut into slices, and the cross section is observed with a transmission electron microscope (hereinafter abbreviated as TEM) to observe the resin coating layer. Observation is performed in four fields of view at 200,000 times magnification per field, and the resin adhesion site of 5 nm or less where the resin adhesion is insufficient is obtained from the outline of the resin layer using image analysis software Win Roof version 5.5 (manufactured by MITANI CORPORATION). Next, the interface length of the aluminum pigment in the field of view is obtained, and the proportion of the resin layer thickness of 5 nm or less where the resin adhesion is insufficient is calculated, and it is defined as [the proportion of the aluminum pigment interface where the resin layer thickness is 5 nm or less (B)].

[0034] The ratio (B) of the interface of the aluminum pigment having a resin layer thickness τ of 5 nm or less, as determined by cross-sectional observation of the resin-adhered aluminum pigment of the present invention, is preferably 5% or less, more preferably 1% or less. When (B) satisfies such a condition, the aluminum particles are entirely covered with the resin, improving chemical resistance.

[0035] In addition, the resin-adhered aluminum pigment of the present invention has a resin layer formed on the surface of the aluminum particles, and therefore has improved chemical resistance in the coating film. When the color difference ΔE is calculated according to 6.3.2 of JIS-Z-8730 (1980) as an evaluation of chemical resistance, it is preferable that ΔE is less than 1.0.

[0036] The resin-adhered aluminum pigments of the present invention can be used in paints and inks. The resin-adhered aluminum pigment of the present invention can be suitably used for automobiles, general home appliances, information appliances such as mobile phones, printing, and coatings for metals such as iron and magnesium alloys, plastics, and other substrates, and can exhibit high design properties. Inks containing the resin-adhered aluminum pigment of the present invention can be suitably used for metallic paints, printing inks, paints for plastic kneading, and the like, and can exhibit high design properties.

[0037] In addition, additives commonly used in the paint industry, such as pigments, dyes, wetting agents, dispersants, color separation inhibitors, leveling agents, slip agents, rheology control agents, viscosity modifiers, antiskinning agents, antigelling agents, defoamers, thickeners, anti-sagging agents, mildew inhibitors, ultraviolet absorbers, film-forming assistants, and surfactants, may be added as appropriate to the novel resin-adhered aluminum pigment of the present invention. EXAMPLES

[0038] The present invention will now be described in detail with reference to examples. In the following description, "%" indicates "% by weight."

[0039] Example 1 100g of commercially available aluminum paste (manufactured by Asahi Kasei Corporation, SB-10 "average particle size 10μm, non-volatile content 74% by mass") was placed in a 1L four-neck flask, 500g of mineral spirits was added, and while bubbling nitrogen gas, a high-speed stirring disperser was used to stir a share disk with a diameter of 8cm at 1000rpm, and the temperature in the system was raised to 70°C. Next, 1.11g of acrylic acid was added and stirring was continued at 70°C for 30 minutes. Next, 10.0g of trimethylolpropane trimethacrylate, 1.11g of di-trimethylolpropane tetraacrylate, 9.5g of 2,2'-azobis-2,4-dimethylvaleronitrile (polymerization initiator), and 50g of mineral spirits were dropped over 1 hour, and polymerization was carried out for a total of 5 hours while maintaining the temperature in the system at 70°C. At this point, the amount of unreacted trimethylolpropane trimethacrylate and di-trimethylolpropane tetraacrylate in the filtrate sampled was analyzed by gas chromatography, and it was found that more than 99% of the added amount had reacted. After the polymerization was completed, the treated slurry was filtered to obtain a resin-attached aluminum pigment. The heating residue of the aluminum pigment (according to JIS-K-5910) was 60.5% by weight. Figures 1 and 2 show FE-SEM images of the resin-adhered aluminum pigment of Example 1. As shown in Figures 1 and 2, resin particles are adhered to the surface of the resin-adhered aluminum pigment of Example 1, and many of them are adhered specifically to edge portions.

[0040] Example 2 A resin-adhered aluminum pigment was obtained in the same manner as in Example 1, except that the amount of 2,2'-azobis-2,4-dimethylvaleronitrile (polymerization initiator) was changed to 11.9 g.

[0041] Example 3 A resin-adhered aluminum pigment was obtained in the same manner as in Example 1, except that the amounts of trimethylolpropane trimethacrylate, di-trimethylolpropane tetraacrylate, and 2,2'-azobis-2,4-dimethylvaleronitrile (polymerization initiator) were changed to 13.3 g, 1.5 g, and 12.7 g, respectively.

[0042] Example 4 A resin-adhered aluminum pigment was obtained in the same manner as in Example 1, except that in Example 3, 2,2'-azobis-2,4-dimethylvaleronitrile (polymerization initiator) was changed to 15.8 g.

[0043] Example 5 A resin-adhered aluminum pigment was obtained in the same manner as in Example 1, except that the ingredients in Example 1 were changed to 100 g of aluminum paste (manufactured by Asahi Kasei Corporation, FD-5060 "average particle size 6 μm, non-volatile content 72 mass%"), 5.2 g of trimethylolpropane trimethacrylate, 0.6 g of di-trimethylolpropane tetraacrylate, and 4.9 g of 2,2'-azobis-2,4-dimethylvaleronitrile (polymerization initiator).

[0044] Example 6 A resin-adhered aluminum pigment was obtained in the same manner as in Example 5, except that the amount of 2,2'-azobis-2,4-dimethylvaleronitrile (polymerization initiator) was changed to 7.4 g.

[0045] Example 7 A resin-adhered aluminum pigment was obtained in the same manner as in Example 1, except that the amounts of trimethylolpropane trimethacrylate, di-trimethylolpropane tetraacrylate, and divinylbenzene were changed to 9.0 g, 1.11 g, and 1.0 g, respectively.

[0046] Example 8 A resin-adhered aluminum pigment was obtained in the same manner as in Example 1, except that the following were changed: 100 g of aluminum paste (manufactured by Asahi Kasei Corporation, MH-8801 "average particle size 15 μm, non-volatile content 65 mass%"), 9.8 g of trimethylolpropane trimethacrylate, 8.8 g of di-trimethylolpropane tetraacrylate, and 8.4 g of 2,2'-azobis-2,4-dimethylvaleronitrile (polymerization initiator).

[0047] Comparative Example 1 100g of commercially available aluminum paste (manufactured by Asahi Kasei Corporation, SB-10 "average particle size 10μm, non-volatile content 74% by mass") was placed in a four-neck flask with a volume of 1 liter, 500g of mineral spirits was added, and the mixture was stirred for 1 hour while bubbling nitrogen gas, and the temperature in the system was raised to 70°C. Next, 1.11g of acrylic acid was added and the mixture was stirred for 30 minutes at 70°C. Next, using a circulating ultrasonic disperser, ultrasonic waves were directly irradiated to the slurry liquid in the container through an ultrasonic horn, and vibration dispersion was performed for 1 hour. Next, 13.3g of trimethylolpropane trimethacrylate, 1.5g of di-trimethylolpropane tetraacrylate, 2.0g of 2,2'-azobis-2,4-dimethylvaleronitrile (polymerization initiator), and 50g of mineral spirits were dropped using a metering pump over 1 hour, and polymerization was performed for a total of 8 hours while maintaining the temperature in the system at 70°C. The amount of unreacted trimethylolpropane trimethacrylate and di-trimethylolpropane tetraacrylate in the filtrate sampled at this point was analyzed by gas chromatography, and it was found that more than 99% of the added amount had reacted. After the polymerization was completed, the treated slurry was filtered to obtain a resin-attached aluminum pigment. The heating residue of the aluminum pigment (according to JIS-K-5910) was 65.2% by weight. Fig. 6 shows an FE-SEM image of the resin-adhered aluminum pigment of Comparative Example 1. As shown in Fig. 6, no resin particles are adhered to the surface of the resin-adhered aluminum pigment of Comparative Example 1.

[0048] Comparative Example 2 A resin-adhered aluminum pigment was obtained in the same manner as in Comparative Example 1, except that the aluminum paste (manufactured by Asahi Kasei Corporation, FD-5060, "average particle size 6 μm, non-volatile content 72 mass%), trimethylolpropane trimethacrylate, and di-trimethylolpropane tetraacrylate were changed to 10.4 g and 1.2 g, respectively.

[0049] Comparative Example 3 A resin-adhered aluminum pigment was obtained in the same manner as in Comparative Example 1, except that the aluminum paste (manufactured by Asahi Kasei Corporation, MH-8801, "average particle size 15 μm, non-volatile content 65 mass%), trimethylolpropane trimethacrylate, and di-trimethylolpropane tetraacrylate were changed to 100 g (4.7 g, 0.5 g).

[0050] Comparative Example 4 A resin-adhered aluminum pigment was obtained in the same manner as in Comparative Example 1, except that the amounts of trimethylolpropane trimethacrylate and di-trimethylolpropane tetraacrylate were changed to 1.4 g and 0.1 g, respectively.

[0051] [Evaluation 1 (average particle size: d50 measurement)] The average particle size (d50) of the aluminum particles was measured using a laser diffraction / scattering type particle size distribution analyzer (LA-300 / HORIBA, Ltd.). Mineral spirits was used as the measurement solvent. The measurements were carried out in accordance with the equipment's instruction manual, but it should be noted that the aluminum particles used as samples were ultrasonically dispersed for 2 minutes as a pretreatment, then placed in the dispersion tank and measurements were started after confirming that the appropriate concentration had been achieved. After the measurement was completed, d50 was automatically displayed.

[0052] [Evaluation 2 (Measurement of the average cross-sectional thickness τ' of aluminum particles)] (1) Preparation of painted panels Using the aluminum pigments obtained in the Examples and Comparative Examples, metallic base paints were prepared according to the following compositions. Aluminum pigment: 2g Thinner (Musashi Paint Co., Ltd., product name "Plaace Thinner No. 2726"): 50g Acrylic resin (Musashi Paint Co., Ltd., product name "Plaace No. 7160"): 33g The above paint was applied to an ABS resin plate using an air spray device so that the dry film thickness was 20 μm, and then dried in an oven at 60° C. for 30 minutes to obtain a metallic base-coated plate. A top coat paint prepared according to the following composition was applied onto the metallic base coated plate using an air spray device. -Hitaroid Varnish 3685S (Hitachi Chemical): 25g Mixed thinner (solvent mixing ratio: toluene: 45% by mass, butyl acetate: 30% by mass, ethyl acetate: 20% by mass, 2-acetoxy-1-methoxypropane: 5% by mass): 20g Duranate TPA100 (Asahi Kasei Chemicals): 5g After the above coating, the plate was dried in an oven at 60° C. for 30 minutes to obtain a coated plate for evaluation.

[0053] (2) Cross-section of the coating Using the coated evaluation plates produced as described above, cross sections of the coating film were prepared according to the following procedure. Using scissors, the coated plate for evaluation was cut into pieces measuring 2 cm square. The cut 2 cm square coated evaluation panels were repeatedly cut along the cross section of the coating using a large rotary microtome (RV-240, manufactured by Yamato Koki Kogyo Co., Ltd.) to remove the microscopic aluminum-acrylic resin protruding from the cross section. The cross-section of the coating film obtained above was subjected to ion milling using an ion milling device (JEOL Ltd. / IB-09010CP) set up so as to be able to irradiate the ion beam up to a portion 20 μm away from the cross-section of the coating film, and a cross-section of the coating film for obtaining an FE-SEM image, as described below, was prepared.

[0054] (3) Obtaining particle cross-sections (FE-SEM images) The coating cross-section (coated plate) obtained in the above ((2) Preparation of coating cross-section) was attached parallel to the SEM sample stage, and a field emission type FE-SEM (Hitachi / S-4700) was used to obtain an FE-SEM image of the coating cross-section. The conditions for FE-SEM observation and acquisition were adjusted so that the acceleration voltage was set to 5.0 kV and the image magnification was 10,000 times. In addition, before acquiring (capturing) the FE-SEM image, electronic axis alignment processing was performed to prevent distortion of the boundary between the aluminum particles and the acrylic resin in the FE-SEM image.

[0055] (4) Analysis (measurement of the average cross-sectional thickness of aluminum particles on the particle cross section) Using the FE-SEM images (10,000x) obtained by the procedure for obtaining particle cross sections (FE-SEM images) described above ((1)-(3)) and image analysis software Win Roof version 5.5 (MITANI CORPORATION), the particle thicknesses at the cross sections of the aluminum particles were measured and the average cross-sectional thickness was calculated. The FE-SEM image for measuring the particle thickness in the cross section of an aluminum particle was displayed, and the ROI line was selected and aligned with the 5 μm scale of the image, and the length and unit were entered and set using the registration / change. Next, the image of the cross-section of the aluminum particle on which the thickness measurement was to be performed was displayed, a rectangular ROI was selected, and the rectangular ROI was aligned with the cross-section of the particle, and binary processing was performed. Next, the subject was asked to select the measurement item of the vertical chord length, and then the measurement was carried out. The value automatically measured by the image analysis software (vertical chord length value) was displayed on the image. In this manner, using the image analysis software Win Roof version 5.5, 100 aluminum particles having an average particle diameter within ±50% of the average particle diameter: d50 described below (IV) average particle diameter: d50 were selected, the cross-sectional thickness of the aluminum particles was automatically measured, and the arithmetic mean value of the 100 particles was calculated to determine the average cross-sectional thickness τ' of the aluminum particles.

[0056] [Evaluation 3 (amount of resin particles per 5 μm at the edge (A) measured by FE-SEM)] The resin-coated aluminum pigment was diluted with an excess of pentane, hand-dispersed for 1 minute, and the resulting solution was air-dried to obtain a measurement sample of the resin-coated aluminum pigment. Next, a field emission FE-SEM (HITACHI / S-4700) was used to obtain an FE-SEM image of the cross section of the coating film of the measurement sample, and the pigment side surface was observed from an angle of 45° and evaluated. The measurement magnification was 20,000 times. The resin-adhered aluminum particles were observed in 30 fields of view, and the number of primary particles (single resin particles) and secondary particles (aggregates of primary particles) resin particles with an area circle equivalent diameter (circle equivalent diameter) of 5 to 50 nm present in an edge portion range of 5 μm at a distance between two points on the edge portion was calculated using the image analysis software Win Roof version 5.5, and the arithmetic average value (A) was calculated.

[0057] [Evaluation 4 (measurement of average surface roughness Ra of resin-adhered aluminum pigment surface)] The surface morphology of the resin-attached aluminum pigment was observed using an atomic force microscope (AFM; Dimensioin Icon (Bruker)). As a pretreatment, the resin-attached aluminum pigment sample was washed with excess methanol, vacuum dried, and dispersed again in acetone, then dropped onto a Si wafer and allowed to dry naturally. A line profile (300 scans) of one field of view, 4 μm square, was obtained using the AFM. The same operation was performed for a total of four or more fields of view, and the arithmetic average value was calculated and taken as Ra. 3(a) and (b) show AFM images of the surface morphology of the resin-adhered aluminum pigment of Example 1.

[0058] [Evaluation 5 (proportion of aluminum pigment interfaces with a resin layer thickness τ of 5 nm or less as measured by TEM (B))] The average thickness τ of the resin layer in the present invention was measured by first ultrasonically cleaning the aluminum pigment with excess methanol and chloroform as a pretreatment, then vacuum drying, dispersing and cleaning again in acetone, and then air drying. The aluminum pigment was then embedded in epoxy resin and completely cured, after which it was trimmed and cut into pieces, and the cross-sections were observed with a TEM to observe the resin coating layer. Four fields of view were observed at 200,000x magnification, and the resin adhesion areas of 5 nm or less where the resin adhesion was insufficient were obtained from the outline of the resin layer using image analysis software Win Roof version 5.5. Next, the interface length of the aluminum pigment in the field of view was obtained, the proportion of the areas with insufficient resin adhesion was calculated, and the arithmetic average proportion (B) was obtained. Figure 4 shows a TEM photograph of a cross section of the resin-adhered aluminum pigment of Example 1. Figure 7 shows a TEM photograph of a cross section of the resin-adhered aluminum pigment of Comparative Example 1. As is clear from Figures 4 and 7, a resin layer is formed on the surface of the aluminum particle.

[0059] [Evaluation 6 (Evaluation of coating adhesion, chemical resistance, gloss retention, and pigment dispersibility)] Using the resin-adhered aluminum pigments obtained in Examples 1 to 8 and Comparative Examples 1 to 4, metallic coating compositions were prepared according to the following formulations. Resin-attached aluminum pigment: 1.3g (solid weight) Thinner (a mixture of 30 parts butyl acetate, 45 parts toluene, 20 parts isopropyl alcohol, and 5 parts ethyl cellosolve): (D) g (the total amount of the resin-attached aluminum pigment and (D) was adjusted to 33 g.) Clear (a mixture of 29 parts of Acrydic A-166 (DIC), 3 parts of nitrocellulose (industrial nitrocellulose 1 / 2AS, Companhia Nitro Qumica Brasileira), and 68 parts of the above thinner) (binder resin component): 42g The resulting coating composition was spray-coated onto an ABS resin plate to a film thickness of 15 μm, and then dried at 55° C. for 30 minutes to prepare a coated plate for evaluation. Using the above-mentioned coating plates for evaluation, the adhesion, chemical resistance, and gloss retention were evaluated.

[0060] (Adhesion of coating film) Using the coated plate prepared above, cellophane tape (registered trademark: CT405AP-18, manufactured by Nichiban Co., Ltd.) was attached to the coating film and pulled at a 45 degree angle, and the degree of peeling of the resin-adhered aluminum pigment particles was visually observed. Depending on the observation results, the following evaluation was made. ○ (Good): No peeling △ (Acceptable): Slight peeling × (Not acceptable): Peeling occurs

[0061] (Chemical resistance of coating film) The lower half of the coated plate prepared above was immersed in a beaker containing 2.5N NaOH aqueous solution and left at 23°C for 24 hours. After the test, the coated plate was washed with water and dried, and the immersed and unimmersed parts were color-measured according to condition d (8-d method) of JIS-Z-8722 (1982), and the color difference ΔE was calculated according to JIS-Z-8730 (1980) 6.3.2. The color difference ΔE was evaluated as follows (the smaller the value, the better). ○ (Good): Less than 1.0 △ (Acceptable): 1.0 or more and less than 2.0 × (not allowed): 2.0 or more

[0062] [Evaluation 7 (FF properties (brightness, lustre), hiding power of coating film)] Using the resin-adhered aluminum pigments obtained in Examples 1 to 8 and Comparative Examples 1 to 4, metallic paints were prepared according to the following compositions. Resin-bonded aluminum pigment: 5.0g Thinner (Kansai Paint Co., Ltd., product name "Acrydic 2000GL"): 13.0g Acrylic resin (Kansai Paint Co., Ltd., product name "Acrydic 2000"): 97.0g Next, the metallic base paint was applied to a PET film using a 3 mil applicator and dried at room temperature for 30 minutes to obtain a metallic base-coated plate. Figure 5 shows a microscope photograph of a metallic base coated plate using the resin-adhered aluminum pigment of Example 1. Figure 8 shows a microscope photograph of a metallic base coated plate using the resin-adhered aluminum pigment of Comparative Example 1. It is clear from Figure 5 that the individual resin-adhered aluminum pigments are uniformly dispersed in the coated plate of Example 1, whereas the resin-adhered aluminum pigments have low dispersibility and are overlapping in the coated plate of Comparative Example 1.

[0063] (2) Measurement of ΔF / F (brightness, luminosity) The paint prepared above was applied to a PET sheet, and the ΔF / F property of the coating film was evaluated using a variable angle colorimeter (manufactured by Suga Test Instruments Co., Ltd.). The incident angle was set at 45 degrees, and the light receiving angle of 15 degrees (L15), which is close to the regular reflection light, and the light receiving angle of 60 degrees (L60), which is close to the base color, were measured, excluding the light in the specular reflection area reflected by the coating film surface of the coating plate for evaluation. The ratio (L15 / L60) was taken as the ΔF / F property.

[0064] (3) Judgment of paint dispersibility Concealment The coating film formed by applying the above-mentioned paint to a PET sheet was visually evaluated. Specifically, the above-mentioned paint was prepared using a standard aluminum paste and a resin-coated aluminum paste, and two painted strips were drawn onto a PET sheet, and a light was shone on the unpainted side to evaluate the hiding power. (The standard aluminum paste pigment is aluminum particles before being coated with resin.) ◎: Has the same hiding power as the standard aluminum paste pigment. ◯: Slightly lower hiding power than the standard aluminum paste pigment. △: The hiding power is low compared to the standard aluminum paste pigment.

[0065] The results of evaluations 1 to 7 are shown in Table 1. [Table 1]

Claims

1. A flat resin-attached aluminum pigment in which the surfaces of aluminum particles are coated with a resin layer containing a polymer of a monomer and / or oligomer having one or more radically polymerizable double bonds, The resin-adhered aluminum pigment has resin particles having a circle-equivalent diameter of 5 to 50 nm adhered to any edge portion of the resin-adhered aluminum pigment.

2. A flat resin-attached aluminum pigment in which the surfaces of aluminum particles are coated with a resin layer containing a polymer of a monomer and / or oligomer having one or more radically polymerizable double bonds, The resin-adhered aluminum pigment has, on an edge portion of the resin-adhered aluminum pigment, 3 to 1,000 resin particles having a circle-equivalent diameter of 5 to 50 nm adhered per 5 μm of the edge portion.

3. 3. The resin-adhered aluminum pigment according to claim 2, wherein 3 to 100 resin particles having a circle equivalent diameter of 5 to 50 nm are adhered to an edge portion of the resin-adhered aluminum pigment per 5 μm of the edge portion.

4. 3. The resin-adhered aluminum pigment according to claim 2, wherein 10 to 100 resin particles having a circle-equivalent diameter of 5 to 50 nm are adhered to an edge portion of the resin-adhered aluminum pigment per 5 μm of the edge portion.

5. 3. The resin-adhered aluminum pigment according to claim 2, wherein the average surface roughness Ra of the resin layer is 2.0 to 7.0 nm.

6. 3. The resin-adhered aluminum pigment according to claim 2, wherein a ratio of a portion of the resin layer having a thickness τ of 5 nm or less is 5% or less, as observed by cross-sectional observation of the resin-adhered aluminum pigment.

7. The resin-adhered aluminum pigment according to claim 2, wherein the aluminum particles have an average cross-sectional thickness τ' of 0.03 to 0.18 μm and an average particle diameter d50 of 5 to 15 μm.

8. A paint comprising the resin-adhered aluminum pigment according to any one of claims 2 to 7.

9. An ink comprising the resin-adhered aluminum pigment according to any one of claims 2 to 7.

Citation Information

Patent Citations

  • Metal pigment and its production

    JP2001115061A

  • Resin coated aluminum pigment

    WO2018047360A1